Students’ Ability in Solving PISA Problems - Septiya Wulandari; Cut Morina Zubainur (Proceedings of AICS - Social Sciences, 2017)
Indonesian students’ achievementin PISA was unsatisfactory. This shows that the problem-solving ability of Indonesian students is still not as expected. This research aims to describe the ability of Indonesian students and the causes of difficulties in solving PISA problems. The study involved 26 students. The data obtained through test and interview. The test was given to students in grade VIII-3 at SMPN 6 Banda Aceh. The interview was conducted with 5 students selected based on criteria, i.e. one student on good ability, one student on fair to good, one student on poor, and two students on very poor ability. The results showed that the students' ability in solving PISA problems was low which is at Level 2 of the 6 levels by The Organization for Economic Cooperation and Development (OECD). In addition, the results also indicated that the causes of the difficulties were because the students unfamiliar to answer the questions that require reasoning. Students were also difficult in understanding about the word problems. Another factor was caused by the lack of students’ ability of mathematical concepts. Keywords:PISA, level of students’ ability, causes of difficulties.